Utilization of wheat bran in finishing swine diets - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1980)
Two trials with finishing pigs were conducted to evaluate wheat bran added to a basal milo-soybean meal diet to provide more crude fiber. Pigs fed added wheat bran (5-10-15-20%) and those fed the basal diet gained similarly, but 40% wheat bran (5.8% crude fiber) signigicant1y reduced rate of gain. Feed per pound of gain was improved approximately 4 to 5% with the addition of 10 or 15% wheat bran; however, cost per pound of gain was the same. Wheat bran usually costing more than milo would not merit its use in swine finishing diets.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Wheat bran; Finishing pigs